Age and Gender as Predictors of Psychological Well-Being - Y. Maroof, Rukhsana; Jahanzeb Khan, Muhammad (The Journal of Humanities & Social Sciences, 2022)
The current study was designed to explore the potential relationship of psychological well-being with age and gender. A sample of 400 individuals, representative of both genders (men=185 & women=215 within an age range of 17 to 50 years) was drawn from various colleges and universities of Khyber Pukhtunkhwa. Ryff’s (1989) psychological well-being scale (middle version consisting of 54 items) was used as a tool to collect the relevant information. According to the results, gender accounted for significant variation in psychological well-being. Men outperformed women on four of six dimensions of psychological well-being (i.e., environmental mastery, personal growth, autonomy, and purpose in life). However, no significant gender differences were found on the aspects of positive relations with others and self-acceptance that indicates that, on average, men and women are alike in these dimensions. A strong relationship was also observed between age and psychological well-being attesting psychological well-being as dependent on age.